Laser assisted micro patterning atop shape memory polymer - Goh, Chee Siew. (2009)
When a Shaped Memory Polymer (SMP) is subjected to external factors like heat, light, moisture etc, it will activate the Shape Memory Effect (SME). When it is heated and temperature is raised to its Glass Transition Temperature (Tg), the material will soften and thus able to be shaped to a desired shape in which it will remain in after it is cooled. This unique ability draws great interests from many industries, including medical field, engineering field and many others. The aim of this project is built on this property of the SMP, in which micro-sized arrays in the form of protrusion bumps and lines will be created onto the SMP surface. SMP has existed for a long time and in the past few years, its usefulness has been illustrated in many industries include the biomedical industry. The SME has been used in many positive aspects in the field. However, SME in micro-level has not yet fulfilled its potential. Therefore, this project will investigate the production on the SMP and then study its effect.